Aplicación de diferentes grosores de mulch para el control del coyolillo (Cyperus rotundus L.) en el cultivo del maíz (Zea mays L.) - Acevedo Ampié, Guillermo; Izabá Ruiz, Raquel (Nexo Revista Científica, 2012)
The control of weeds in cultivation might become a problem depending on the kind of crop, control conditions and its own resistance to specific products or operating forms. Present research has as it´s the evaluation objective the effect of different lesser thicknesses of mulch equal to 10 cm in the control of the growth of nut grass (Cyperus Rotundus) in the maize culture. A complete block design with five treatments and three replications was randomly used, the variables were as follows: number of nut grass in one square meter, height of coyolillo, the diameter of corn ears, length of ears, number of seeds per row, number of row per ears and yield The results show with the treatments at mulch of 8 and 10 cm. an effective control of nut grass occurs (Cyperus Rotondus). We can conclude that the control of nut grass with mulch should be practiced by the producers often as possible because its a practice of effective control, and aid to the conservation of the environment, using residues from cultivation and familiar manual labor. Keywords: weeds, control of growth, complete block design.